Czy można zbudować pełną teorię wartości? (Świat Idei i Polityki, 2009)
The considerations of scientists interested in political ethics about theory of values are related to the fields that aim to built an entire theory of axiological phenomena concerning history, sociology, political science and economy. (However, they do not explain all the moral problems.) In the article there are analyzed the definitions of values (with the moral evaluations) as well as the theories and systems of values. Besides, a classification of the contemporary ethical theories has been presented. The most important values are explain. It turns out that they do not must be treated with concrete social, political or economical assumptions. They emphasize, however -in majority- the independence, impartiality, value relativism and rationality of arguments. The most important of the contemporary theories of values are: the formalism, the utilitarism, the ethics of virtue and the ethics of love. After analyzing the sources, it seems that it is impossible yet to create an entire (one, general and universal) theory of values. Thus, the answer to the title question is negative.